2019
DOI: 10.1108/ilt-09-2019-0398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish scale texture on friction performance for reciprocating pair with high velocity

Abstract: Purpose This paper aims to study the frictional performance of reciprocating pair with high velocity by using hydrodynamic lubrication principle and fish scale textured piston model. Design/methodology/approach Based on the idea of function characteristic approximation and coordinate change, a mathematical representation model of imitating fish scale texture pit section is established. According to the principle of dynamic pressure lubrication of the textured fluid, a three-dimensional numerical model of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…They proposed that, under water lubrication, biomimetic samples with enhanced wettability would generate a thicker lubricating film on their surface, resulting in a 7.3% reduction in friction coefficient [22]; Yang et al utilized laser processing to create a bionic anti-fog superhydrophilic micro-surface structure with a honeycomb pattern on glass substrates. They concluded that the enhancement of glass hydrophilicity and wettability was associated with an increase in the contact angle of the honeycomb structure [23]; Song et al through orthogonal testing and FLUENT software analysis, examined piston sub-samples featuring carp scale texture characteristics and suggested that fish scale textures could significantly enhance the frictional and lubrication performance of high-speed reciprocating piston subsurfaces under lubricated conditions [24]; Vidyasagar et al using nanosecond fiber laser processing, created Mamba snake skin texture on radial ball bearings' end faces as samples. Compared to conventional bearings, these snake skin textured bearings exhibited superior friction dynamics and lubrication performance under lubricated conditions [25]; Zhang et al inspired by shark skin surface texture, developed a bionic pinion and rack structure with diamond patterns; they proposed that bionic pinions and racks with different texture parameters demonstrated improved frictional properties and wear resistance compared to traditional structures [26].…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that, under water lubrication, biomimetic samples with enhanced wettability would generate a thicker lubricating film on their surface, resulting in a 7.3% reduction in friction coefficient [22]; Yang et al utilized laser processing to create a bionic anti-fog superhydrophilic micro-surface structure with a honeycomb pattern on glass substrates. They concluded that the enhancement of glass hydrophilicity and wettability was associated with an increase in the contact angle of the honeycomb structure [23]; Song et al through orthogonal testing and FLUENT software analysis, examined piston sub-samples featuring carp scale texture characteristics and suggested that fish scale textures could significantly enhance the frictional and lubrication performance of high-speed reciprocating piston subsurfaces under lubricated conditions [24]; Vidyasagar et al using nanosecond fiber laser processing, created Mamba snake skin texture on radial ball bearings' end faces as samples. Compared to conventional bearings, these snake skin textured bearings exhibited superior friction dynamics and lubrication performance under lubricated conditions [25]; Zhang et al inspired by shark skin surface texture, developed a bionic pinion and rack structure with diamond patterns; they proposed that bionic pinions and racks with different texture parameters demonstrated improved frictional properties and wear resistance compared to traditional structures [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al [15] studied the improvement in tribological properties after surface micro-texturing using chemical solutions. It was also shown theoretically that biomimetic texture morphologies significantly improve the tribological response through increased oil retention [16][17][18]. In the past decade, surface laser texturing has been recognised as an effective technique in enhancing the tribological performance of materials [19][20][21][22] due to its short processing times, good control over the process and friendliness to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, there is still a gap to fill by exploring new techniques. Recently, some scholars observed and studied the surface morphology of earthworms [8], pangolins [9], snakes [10], fishes [11], snails [12], and other organisms, and found that these surface morphologies usually have good properties of desorption, anti-adhesion and wear resistance [13]. Inspired by the biological surface morphologies, the non-smooth surface has been successfully applied to multiple occasions with relative motion, e.g., bearings [14], cylinder liners [15], mechanical seals [16], and cutting tools [17], to improve the tribological properties [18].…”
Section: Introductionmentioning
confidence: 99%